 #1
VVS2000
 145
 17
 Homework Statement:
 The problem was to show that given φ(p), and wave function Ψ(r), prove that <p>= ∫φ(p)*pφ(p)dp and <p²>=∫φ(p)*p²φ(p)dp
 Relevant Equations:

Ψ(r)=1/2πℏ ∫ φ(p)exp(ipr/ℏ)dp
<p>=∫Ψ(r)*pΨ(r)dr
so from Fourier transform we know that
Ψ(r)=1/2πℏ∫φ(p)exp(ipr/ℏ)dp
I proved that <p>= ∫φ(p)*pφ(p)dp from <p>=∫Ψ(r)*pΨ(r)dr
so will the same hold any operator??
Ψ(r)=1/2πℏ∫φ(p)exp(ipr/ℏ)dp
I proved that <p>= ∫φ(p)*pφ(p)dp from <p>=∫Ψ(r)*pΨ(r)dr
so will the same hold any operator??